Brodalumab to the Rescue: Efficacy and Safety of Brodalumab in Patients with Psoriasis and Prior Exposure or Inadequate Response to Biologics - Alan Menter; April Armstrong; Abby Van Voorhees; Clive Liu; Abby Jacobson (Dermatology and Therapy, 2020)
Abstract While biologic therapies for psoriasis are effective for many patients, some patients may lose response, have inadequate control of disease, or develop intolerance to certain biologic agents. It may therefore be beneficial for patients whose psoriasis fails to respond to one biologic to switch to a different biologic therapy, in particular one with a different mechanism of action. However, it remains unclear how prior biologic exposure or lack of response affects the efficacy and safety of subsequent biologics in patients with moderate-to-severe psoriasis. Brodalumab, a fully human anti-interleukin-17 receptor A monoclonal antibody, has previously been shown to be efficacious in treating moderate-to-severe psoriasis in three large phase 3 trials (AMAGINE-1, AMAGINE-2, and AMAGINE-3). In this review, we summarize the efficacy and safety of brodalumab in patients with moderate-to-severe psoriasis and a history of biologic exposure. Further, we describe improvements in skin clearance and quality of life measures as well as safety in patients who had inadequate response to ustekinumab and who were rescued with brodalumab therapy. Lastly, we discuss improvements in skin clearance following rescue with brodalumab in patients whose disease failed to respond to secukinumab and ixekizumab. The findings of our review suggest that brodalumab is a safe and efficacious treatment regardless of past biologic use or lack of response to prior biologic therapy.